Comparison of Dimensional Stability and Surface Detail Reproduction of Silicone Based Impression Materials - Karki, Riwaj; Naulakha, Dipendra (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 68-73 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8809